Trakthyggesfria skogsbrukssätt : kunskap, förutsättningar och attityder - Hagegård, Erika (SLU/Dept. of Forest Products, 2006)
Forestry has three main aspects to take into consideration today; economical, ecological and socio-cultural. In order to reach the broad policy goals for sustainable forest management, an increased variety of management approaches are requested. Today clear-cutting is the only method used in 96 % of the managed forests in Sweden. The Swedish National Board of Forestry has therefore initiated a project in order to investigate and develop Continuous Cover Forestry (CFF). This study is a part of this project. The aim was to increase the knowledge on how much different stakeholders knew about CCF, the practical prerequisites and the attitudes related to inclusion of CCF in their management. Interviews were made in two different Swedish forest-regions, Bergslagen in the south and Västerbottens län in the north. Semi-qualitative data was collected from 22 Non-Industrial Private Forest Owners (NIPF), representatives for forest commons, forest companies as well as professional foresters. When talking to the local stakeholders a "bottom-up-approach" was used in order to increase the understanding of how policy intentions can be transformed into practical action. The results showed that the respondents had knowledge about CCF, but mainly about the management methods that were common before clear-cutting was introduced. Most respondents saw CCF more as nature conservation rather than a way of management. The practical possibilities were rather good. The main problems seemed to be profitability, and lack of experience. The attitudes varied strongly. Most respondents agreed on that socio-cultural and ecological values would increase with CCF. Half of the respondents thought that it would have negative impact on the economy, while the rest thought that CCF could, at least partly, improve the economy. Only two respondents were positive to the Swedish forest policy with equal environmental- and productions goals. A clear difference between the two areas was that more respondents in Bergslagen had other goals than economical with their forestry. To implement a policy into practical action it is important to have knowledge about the target group, in this case the forest owners. A forum is needed, where stakeholders can meet and discuss forest management.